2014
DOI: 10.1073/pnas.1401950111
|View full text |Cite
|
Sign up to set email alerts
|

FAM65B is a membrane-associated protein of hair cell stereocilia required for hearing

Abstract: In a large consanguineous Turkish kindred with recessive nonsyndromic, prelingual, profound hearing loss, we identified in the gene FAM65B (MIM611410) a splice site mutation (c.102-1G>A) that perfectly cosegregates with the phenotype in the family. The mutation leads to exon skipping and deletion of 52-amino acid residues of a PX membrane localization domain. FAM65B is known to be involved in myotube formation and in regulation of cell adhesion, polarization, and migration. We show that wild-type Fam65b is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 22 publications
2
68
0
3
Order By: Relevance
“…As members of this family are broadly expressed in many tissues and cell types, we anticipate that this family of proteins will have broad physiological and pathophysiological functions. Indeed, a mutation in the human FAM65B gene has recently been associated with hearing loss (Diaz-Horta et al, 2014). Future studies are needed to determine whether the phenotype is related to RHOA regulation.…”
Section: Discussionmentioning
confidence: 99%
“…As members of this family are broadly expressed in many tissues and cell types, we anticipate that this family of proteins will have broad physiological and pathophysiological functions. Indeed, a mutation in the human FAM65B gene has recently been associated with hearing loss (Diaz-Horta et al, 2014). Future studies are needed to determine whether the phenotype is related to RHOA regulation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In addition, the lateral line of zebrafish is externally exposed, which makes lateral line hair cells good candidates for experimental manipulations. Furthermore, external fertilization and optically transparent embryos allow the inner ear of zebrafish embryos to be easily accessible for live imaging and physiological recording.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,[8][9][10][11] Overall, these advantages of the zebrafish make it an ideal and convenient model for research on inner ear hair cell death and regeneration, drug screens for ototoxins and otoprotectants, and discovery of new genes for sensorineural deafness. [3][4][5][12][13][14][15][16] Several studies have reported important developmental stages of morphology of the zebrafish inner ear. At 16 hours postfertilization (hpf), the otic vesicle of zebrafish starts to form, and at about 19 hpf, two tiny otoliths become visible at the anterior and posterior ends of the otic vesicle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although FAM65A only associates with active RHO proteins, interaction of FAM65B with RHOA seems to be constitutive (Rougerie et al, 2013;Gao et al, 2015). Second, FAM65A and FAM65B seem to localise differently within the cell, with FAM65B being primarily localised to the plasma membrane (Diaz-Horta et al, 2014;Gao et al, 2015), as opposed to the Golgi and cytoplasmic punctae containing FAM65A. Nevertheless, we have observed that loss of FAM65A can trigger RHO hyper-activation (Fig.…”
Section: E-2mentioning
(Expert classified)